Peningkatan Kemampuan Berdiskusi dengan Penggunaan Metode Pembelajaran Kooperatif Tipe Numbered Head Together Siswa Kelas VIII F SMPN 1 Padangpanjang - Mandasari, Fitria; Emidar, Emidar; Arief, Ermawati (Universitas Negeri Padang, 2012)
The research is to describe the increasing of the learning discuss the use of cooperative learning methods Numbered Heads Together type of student in the class VIII F SMPN 1 Padang Panjang wich is from indicators of pronunciation, grammar, liveliness ask class in questions, connection and topic, and the conversation. This research was classroom action research that descriptive methods. The data obtained through observation sheets, field notes, questionnaires, and performance tests. This study was conducted in three cycles, each cycle conducted in two meetings. Based on the results of this research obtained conclude that the use of cooperative learning methods of the type Numbered Heads Together to improve the learning ability of students to discuss class VIII F SMPN 1 Padang Panjang. The increase is seen in the acquisition value of the average room in the count is significant,Â prasiklus 53.90%, 63.62% first cycle and the second cycle of 76.62%.